SOME OF ANTHROPOLOGICAL CHARACTERISTICS WITH TECHNIQUE RUNNING IN MIDDLE DISTANCE - Rade Stefanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Human muscular system has a large number of innate slow contractile fibres which means that increase of oxygen absorption level can be achieved by adequate training. An athlete who is very good at performing activities which take endurance as well as at explosive strength activities, represents an ideal middle-distance runner who has rather even relation of both types of muscle fibres. This explains why a talented runner such as Steve Ovet achieved much better results than contemporary runners on middle-distance tracks. Besides, there are also some other things which are necessary: a healthy and strong heart, large capacity of lungs, optimal body proportions, basic speed impro¬ve¬ment, development of good running techniques as well as improvement of oxygen absor¬ption with improvement of tolerance for lack of oxygen. Mutual dependence of aerobic and anaerobic processes in running disciplines is different, what can be seen from the tables. However, it does not necessarily mean that tabular processes represent relations which should be observed in relation to length and load of training.